Okun's Law in Australia1. Issue 295 (1st September 2015) - Valadkhani, Abbas
Abstract : This paper examines the dynamic behaviour of the Okun coefficient using quarterly data (1980Q3–2014Q1). It is found that a rise in labour productivity and a fall in output can increase unemployment. A 1 per cent reduction in the unemployment rate requires only a 2.4 per cent increase in real output growth above the average growth rate, but during recessions this figure increases to 4.53 per cent. The probability of observing a higher coefficient was limited to recessionary periods. Given that recessions are now less frequent, Okun's law continues to be a useful rule of thumb in Australia.